2005
DOI: 10.1177/0363546504268037
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Anterior Shoulder Stabilization of Collision and Contact Athletes

Abstract: One hundred percent of all collision and contact athletes returned to organized high school or college sports. Fifteen percent of those collision athletes had a recurrence, which has not required treatment. Participation in collision and contact athletics is not a contraindication for arthroscopic anterior shoulder stabilization using suture anchors, proper suture placement, capsulorrhaphy, and occasional rotator interval plication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
223
6
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(248 citation statements)
references
References 23 publications
5
223
6
14
Order By: Relevance
“…The reliability of this new tool however needs to be confirmed by specific studies as it has not yet been validated. The results concerning return to sports are similar to those reported in the literature [17,24,25,27]. Concerning apprehension, we found that, regardless of the procedure performed; about 20% of shoulders had persistent anterior apprehension (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The reliability of this new tool however needs to be confirmed by specific studies as it has not yet been validated. The results concerning return to sports are similar to those reported in the literature [17,24,25,27]. Concerning apprehension, we found that, regardless of the procedure performed; about 20% of shoulders had persistent anterior apprehension (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…과거 전방 불안 정성의 수술적 치료는 비교적 높은 재발률을 나타 냈으나 최근 관절경적 술식 및 봉합 고정 나사못 의 발달로 여러 학자가 Bankart 재건술 후 10% 내외의 비교적 좋은 결과를 보고하고 있다 1,12,24,25) .…”
Section: 불안정성의 재발unclassified
“…These include young age, high level of athletic competition, presence of a bony defect in the glenoid or humeral head, number of suture anchors, and ligamentous laxity. [12][13][14] The purpose of our study was to retrospectively evaluate the outcomes of arthroscopic repair of capsulolabral lesions in patients enrolled in our institution's database, with a minimum follow-up of one year.…”
Section: Introductionmentioning
confidence: 99%